The girl who loved Tom Gordon : [compact disc, unabridged] - King, Stephen, 1947- (Encore/Simon & Schuster Audio, 2008)
Nine-year-old Trisha McFarland, on a hike in the Maine woods with her brother and recently divorced mother, steps off the trail and suddenly finds herself lost. As Trisha wanders the woods, the listener is given the back story of her family, friends, fears, and triumphs. King vividly depicts Trisha's psychological turmoil, from the first fluttering of nervous disorientation to full-blown hallucinations. And, as Trisha clings to sanity, listeners will certainly root for her rescue.